2019
DOI: 10.1177/1747493019827763
|View full text |Cite
|
Sign up to set email alerts
|

High in-hospital blood pressure variability and severe disability or death in primary intracerebral hemorrhage patients

Abstract: Objective To quantify in-hospital systolic blood pressure variability among patients with intracerebral hemorrhage, determine the association between high systolic blood pressure variability (HSBPV) and 90-day severe disability or death, and examine the association between pre-hospital factors and HSBPV. Methods Adult, radiologically confirmed, intracerebral hemorrhage patients enrolled in a multi-site cohort were included. Using a semi-automated algorithm, systolic blood pressure values recorded from routine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Moreover, SBP-CV predicted poor outcome better than DBP-CV according to ROC curves. Several previous studies have demonstrated that there is a stronger predictive function of short-term and longterm SBPV than DBPV in patients with ischemic or hemorrhagic stroke (Rothwell et al, 2010;Geeganage et al, 2011;Endo et al, 2013;Rodriguez-Luna et al, 2013;Chung et al, 2018;Divani et al, 2019;Meeks et al, 2019). This finding suggests that SBPV is more critical than DBPV for ICH prognosis, not only in short-term and long-term recordings, but also in beat-tobeat measurements.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, SBP-CV predicted poor outcome better than DBP-CV according to ROC curves. Several previous studies have demonstrated that there is a stronger predictive function of short-term and longterm SBPV than DBPV in patients with ischemic or hemorrhagic stroke (Rothwell et al, 2010;Geeganage et al, 2011;Endo et al, 2013;Rodriguez-Luna et al, 2013;Chung et al, 2018;Divani et al, 2019;Meeks et al, 2019). This finding suggests that SBPV is more critical than DBPV for ICH prognosis, not only in short-term and long-term recordings, but also in beat-tobeat measurements.…”
Section: Discussionmentioning
confidence: 85%
“…BPV is primarily divided into the three following categories: long-term (days to months), short-term (minutes to hours), and very shortterm (beat-to-beat) BPV (Parati et al, 2013). Most previous studies in patients with ICH have focused on the first two types of BPV and have reported that an increased BPV during both acute and subacute stages was independently associated with worse functional outcomes at 3 months (Manning et al, 2014;Tanaka et al, 2014;Lattanzi et al, 2015;Chung et al, 2018;de Havenon et al, 2018;Meeks et al, 2019). Tanaka et al and Rodriguez-Luna et al further revealed that SBPV was correlated with early neurological deterioration (Rodriguez-Luna et al, 2013;Tanaka et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, HR variability was not affected by the overlap time or number of enteral antihypertensives used, which might be related to the class of antihypertensive agents used during this process. Previous studies have investigated SBPV using IV antihypertensive agents in patients with ICH and SAH (13)(14)(15)(20)(21)(22). In a study by Liu-DeRyke et al, 28 patients on labetalol were compared to 26 patients receiving nicardipine.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with TIA or ischemic stroke, BP variability is associated with an increased risk of vascular events, including stroke, coronary artery disease, and heart failure [ 133 , 134 ]. In ICH patients, high in-hospital BP variability is associated with severe disability or death, especially elderly patients, female patients, and patients with high admission SBP [ 135 ]. In these cases, antihypertensive drugs should target a lowering of both mean BP and BP variability.…”
Section: Discussionmentioning
confidence: 99%